2017
DOI: 10.1097/bot.0000000000000941
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Topical Antibiotics for Infection Prophylaxis in Pelvic and Acetabular Surgery

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 39 publications
0
48
1
Order By: Relevance
“…A previous meta-analysis with a limited quality of evidence showed a significant protective effect of topical vancomycin powder in reducing SSI rate in spinal surgery. 44 Owen et al 45 reported in a recently published cohort study a significant reduction of postoperative infection if vancomycin or tobramycin powder were applied in pelvic/acetabular fracture surgery. In open articular tibial fractures, Singh et al 18 found no beneficial effect of topical vancomycin, although this study is associated with a considerable risk of bias due to a small sample size and inadequate reporting of soft-tissue involvement and length of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…A previous meta-analysis with a limited quality of evidence showed a significant protective effect of topical vancomycin powder in reducing SSI rate in spinal surgery. 44 Owen et al 45 reported in a recently published cohort study a significant reduction of postoperative infection if vancomycin or tobramycin powder were applied in pelvic/acetabular fracture surgery. In open articular tibial fractures, Singh et al 18 found no beneficial effect of topical vancomycin, although this study is associated with a considerable risk of bias due to a small sample size and inadequate reporting of soft-tissue involvement and length of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, calcium sulfate use has been associated with aseptic seroma and wound drainage issues [13 , 41] . With regards to vancomycin-induced nephrotoxicity, previous orthopedic literature has not shown significant risk for renal injury with vancomycin powder [42][43][44] or vancomycinimpregnated calcium sulfate [16] . While these were not reported in the present study, further examination and vigilance is needed for these issues in the continued use of calcium sulfate adjuncts.…”
Section: Discussionmentioning
confidence: 97%
“…While Stoppa and modified Stoppa approach have shown lower rates of blood loss than the ilioinguinal approach, 23 no difference in infection or complication rate has been reported to date after pelvic fracture stabilization. 24 It has been proposed that topical antibiotics may reduce the incidence of surgical site infection after open pelvic and acetabulum fixation, 25 which may be a viable infection reduction strategy in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%